INNOVATIVE STRATEGY OF THE HEAD OF SASANA JAYA MONASTERY IN CRISIS MANAGEMENT - Dewi, Metta Puspita (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2024)
The head of The Sasana Jaya Buddhist Monastery manages all threats, makes quick decisions, and monitors the development of the crisis. This study aims to describe the innovative strategies of the monastery's head in facing health, social, economic, spiritual, and educational challenges as a form of crisis management in response to COVID-19. This research is qualitative and employs a case study method. Data collection uses observation, interview, and documentation techniques. The validity of the data is ensured through credibility, transferability, dependability, and confirmability tests. Data analysis involves data collection, data reduction, data presentation, and conclusion drawing. Strategies in the social sector include the distribution of basic necessities, masks, and vitamins. Innovative strategies in the economic field include fundraising through kathina, pattidana, and puja pelita activities to maintain the operation and existence of the monastery. Educational innovation is achieved through online learning media via WhatsApp groups. The aspect of faith is reinforced through the recitation of the Ratana Sutta during every puja